O apagamento de /d/ em morfema de gerúndio na fala de Feira de Santana-Ba - Santos, Marcelo dos (2021)
This dissertation presents results of a research about the deletion of the stop /d/ in the morpheme –ndo, indicator of gerund, in Brazilian Portuguese. It is assumed that the researched phenomenon is a rule of variable nature in which the binary dependent variable is characterized by the maintenance or deletion of /d/ in the morpheme of gerund as in cantando (standard form) and cantano(non-standard form). The theoretical-methodological framework is the Variationist Sociolinguistics (WEINREICH; LABOV; HERZOG, 2006 [1968]; LABOV, 2008 [1972]). The study was carried out based on 24 sociolinguistic interviews from the city of Feira de Santana-BA, selected from the database of the project “A Língua Portuguesa no Semiárido Baiano”(UEFS). The objective of the research is to describe how the phenomenon is conditioned according to structural and social factors, as well as to observe, in apparent time, if there are signs of linguistic change taking place in the researched community. The social variables controlled were ‘education’, ‘sex’ and ‘age group’, and the linguistic variables were ‘verbal conjugation’, ‘verb length’, ‘following context’ and ‘syntactic structure’. The data were analyzed quantitatively using the computational tool GoldVarb X (SANKOFF; TAGLIAMONTE; SMITH, 2005). The results indicate usage rate of 67.7% of the non-standard variant in the corpus. The variable phenomenon is conditioned by linguistic and extralinguistic factors and the variables ‘education’, ‘sex’, ‘following context’, ‘age group’ and ‘verb length’ were statistically relevant in this order of selection.